Application of the Principles of Management of Village-Owned Enterprises (BUMDes) to Village Economic Development in Tegal Harum Village, West Denpasar District - Da Costa Soares, Belicia Esperanza Constantine Manuella; Saraswaty, Amrita Nugraheni (CV. Rayyan Dwi Bharata, 2025)
Economic development is an important part of national development. Development is an effort carried out with the aim of improving the standard of living and welfare of the community. The gap between rural and urban economic development is apparent in many regions, with rural areas often lagging behind in terms of infrastructure, technological progress, and income growth. To address this gap, various rural development initiatives, including the establishment of Village-Owned Enterprises (BUMDes), have been implemented. This research aims to determine the influence of the principles of cooperative, participatory, emancipatory, transparent, accountable and sustainable Village-Owned Enterprises (BUMDes) simultaneously on village economic development in Tegal Harum Village, West Denpasar District, and to analyze the influence of the principles of Owned Enterprises Cooperative, participatory, emancipatory, transparent, accountable and sustainable villages (BUMDes) have a partial influence on village economic development in Tegal Harum Village, West Denpasar District. Using BUMDes Puspa Harum Sejahtera in Tegal Harum Village as a case study, this research assesses changes in community income before and after the establishment of BUMDes. BUMDes Puspa Harum Sejahtera has achieved significant success at the local, provincial and national levels, contributing greatly to village income and development. The findings of this study show that structured and transparent BUMDes management can significantly increase village income and encourage sustainable economic development. The results of this research provide valuable insights for policy makers and rural development practitioners, emphasizing the role of BUMDes in alleviating poverty and empowering the local economy.